Oil Trade and Climate Policy - Malik Curuk; Suphi Sen (Center for Economic Studies and ifo Institute (CESifo), 2015)
It has been argued that a depletable resource owner might optimally increase near-term supply in response to environmental policies promoting the development of alternative resources, which might render climate policy ineffective or even counterproductive. This paper empirically confirms this prediction using data on crude oil exports from OPEC to OECD countries between 2001-2010 in a gravity framework. It documents that oil exporters decrease prices and increase quantity of oil exports in response to increases in R&D intensity on renewable energy technologies in importer countries. We further show that (i) these findings are mainly driven by the exporters with higher dependence on oil revenues; (ii) the Armington elasticity of oil is about 2.4; and (iii) exports of coal, which is in abundant supply, are not significantly affected by the changes in R&D intensity of importer countries. Besides having important implications for the effectiveness and design of climate policy, these results underscore the role of dependence on oil revenues of the oil exporters and economic/political diversification incentives of the importer countries in the oil markets.
Keywords: F10; Q40; Q50; 330; climate policy; oil trade; gravity equation; Green Paradox